2018
DOI: 10.1111/jdv.14843
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fungal fluorescent staining and ITS rDNA PCR‐based sequencing with conventional methods for the diagnosis of onychomycosis

Abstract: BackgroundThe current gold standard for diagnosing onychomycosis is direct microscopic examination and culturing. Fungal culture is a time‐consuming procedure, while direct microscopy of potassium hydroxide (KOH) mounts suffers from low sensitivity. More rapid and sensitive methods for the diagnosis of onychomycosis are in high demand.ObjectiveTo establish an effective method for the diagnosis of onychomycosis by assessing the efficacies of fungal fluorescent staining and internal transcribed spacer (ITS) ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Another method is the PCR technique, which can determine the causal agent by amplification of 18S rRNA. All of these techniques are not 100% effective, so a combined use allows a better identification, decreasing false negatives [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Another method is the PCR technique, which can determine the causal agent by amplification of 18S rRNA. All of these techniques are not 100% effective, so a combined use allows a better identification, decreasing false negatives [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Non‐dermatophyte moulds cause about 10% of the onychomycoses with a range from 1.45% to 17.6% . Fusarium spp alone were estimated at 1%‐6% of onychomycoses, but were found in a higher percentage in other studies .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other methods, Lubis et al 20 and Bao et al 21 reported the use of DNA methods such as real-time PCR and restriction fragment length polymorphism to detect possible fungal infection, and to improve the reliability of questionable fungal test results based on current sensitivity and specificity data. Using DNA detection methods provided higher sensitivity and specificity, indicating that both could be improved.…”
Section: Discussionmentioning
confidence: 99%